Saving Space with Foldable Single Bed for Single Household - Maliki, Mohamad Raimi Iskandar; Sidek, Ahmad Anwar Safwan (Research in Management of Technology and Business, 2025)
A development of a single bed that can save space inside a bedroom to because bed is one of the largest horizontal furniture in a bedroom that can take a lot of spaces and this study will help to make the bed design become space saving furniture to solve the problem mention by Hussein Ali Hussein in 2020 where he mention that traditional furniture occupy a lot of space in a small household. The objectives of the study are to identify the design characteristic of a foldable single bed, to design a foldable single bed that can save space and to produce a foldable single bed prototype that can save space. The study is conducted with the collected of 162 respondents consist of individual who are 18 years and above who are living in a single household and those who plan to purchase a single bed in the area of Batu Pahat, Johor. The results were achieved through the distribution of online questionnaire which is Google Form. The design later finalize in 3D CAD software to simulate real life bed and bedroom comparison. The prototype are created with squared hollow metal with vary size and 12mm plywood. The study aim to design a single bed with respondents’ preferences which are the height of the respondent, the design of single bed in the market, and the preferred features and design criteria that the respondent wanted. This study was anticipated could contribute as on the solution to solve the problem of the big size of single bed that can cause a lot of irregularity and wasted spaces in a bedroom. The prototype has been found to consume less space in a bedroom as aim for the objective. The foldable bed also show that it is easy to handle when cleaning the bed area as it is has the mechanism needed to flip and clean under the bedside.